Neuronal low-density lipoprotein receptor-related protein 1 binds and endocytoses prion fibrils via receptor cluster 4. - Jen, A; Parkyn, C; Mootoosamy, R; Ford, M; Warley, A; Liu, Q; Bu, G; Baskakov, I; Moestrup, S; McGuinness, L; Emptage, N; Morris, R (2010)
For infectious prion protein (designated PrP(Sc)) to act as a template to convert normal cellular protein (PrP(C)) to its distinctive pathogenic conformation, the two forms of prion protein (PrP) must interact closely. The neuronal receptor that rapidly endocytoses PrP(C) is the low-density lipoprotein receptor-related protein 1 (LRP1). We show here that on sensory neurons LRP1 is also the receptor that binds and rapidly endocytoses smaller oligomeric forms of infectious prion fibrils, and recombinant PrP fibrils. Although LRP1 binds two molecules of most ligands independently to its receptor clusters 2 and 4, PrP(C) and PrP(Sc) fibrils bind only to receptor cluster 4. PrP(Sc) fibrils out-compete PrP(C) for internalization. When endocytosed, PrP(Sc) fibrils are routed to lysosomes, rather than recycled to the cell surface with PrP(C). Thus, although LRP1 binds both forms of PrP, it traffics them to separate fates within sensory neurons. The binding of both to ligand cluster 4 should enable genetic modification of PrP binding without disrupting other roles of LRP1 essential to neuronal viability and function, thereby enabling in vivo analysis of the role of this interaction in controlling both prion and LRP1 biology.